2021
DOI: 10.1038/s41467-021-21063-0
|View full text |Cite
|
Sign up to set email alerts
|

Structural elements in the flexible tail of the co-chaperone p23 coordinate client binding and progression of the Hsp90 chaperone cycle

Abstract: The co-chaperone p23 is a central part of the Hsp90 machinery. It stabilizes the closed conformation of Hsp90, inhibits its ATPase and is important for client maturation. Yet, how this is achieved has remained enigmatic. Here, we show that a tryptophan residue in the proximal region of the tail decelerates the ATPase by allosterically switching the conformation of the catalytic loop in Hsp90. We further show by NMR spectroscopy that the tail interacts with the Hsp90 client binding site via a conserved helix. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 90 publications
3
39
0
Order By: Relevance
“…p23 consists of a globular CS (CHORD and Sgt1) domain and a largely disordered charged C-terminal tail. We have recently demonstrated that the p23 tail contains a helical segment that weakly interacts with the MD-CTD interface of Hsp90 and with GR, free or in complex with Hsp90 ( 57 ). Similar interactions are observed in a cryo-EM structure of the maturation complex of GR-Hsp90-p23 ( 18 ), and direct interactions have been previously reported for the p23 tail and p53 ( 24 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…p23 consists of a globular CS (CHORD and Sgt1) domain and a largely disordered charged C-terminal tail. We have recently demonstrated that the p23 tail contains a helical segment that weakly interacts with the MD-CTD interface of Hsp90 and with GR, free or in complex with Hsp90 ( 57 ). Similar interactions are observed in a cryo-EM structure of the maturation complex of GR-Hsp90-p23 ( 18 ), and direct interactions have been previously reported for the p23 tail and p53 ( 24 ).…”
Section: Resultsmentioning
confidence: 99%
“…The transient and weak interactions of the p23 C-terminal region can be displaced by clients. The subsequent binding of the C-terminal tail of p23 to the bound client ( 57 ) results in a stabilization of the ternary complex.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is proposed that the inhibition of ATPase activity by p23 allows Hsp90 to maintain its closed state 2 conformation which has a high affinity for client proteins [30]. Closed state 2 has been recognized as an important step in client protein maturation due to its increased client affinity [30,31]. There is also evidence of FKBP51 binding along with p23 at this stage suggesting these complexes may be specific to FKBP51-recruited clients [32].…”
Section: Hsp90 Chaperone Cycle and Functionmentioning
confidence: 99%
“…It is believed that the ability of eukaryotic Hsp90 to act on structurally and functionally dissimilar clients stems from its structural plasticity, which is tuned by the effect of co-chaperone binding on the conformational equilibria within the ATPase cycle. 16 , 17 The structural evidence for this plasticity has been obtained from fluorescence resonance energy transfer (FRET), 18 23 single-angle X-ray scattering (SAXS), 24 X-ray crystallography/cryo-electron microscopy (cryo-EM), 25 28 nuclear magnetic resonance (NMR), 29 , 30 and recently double electron–electron resonance (DEER) 31 experiments. The hydrolysis conformational cycle of Hsp90 in the presence of just nucleotides (ATP, AMP-PNP, and ADP) is now well established with Hsp90 found in an equilibrium between two sets of conformations termed open and closed, with respect to the dimerization of the NTDs.…”
mentioning
confidence: 99%